Introgression of tsv1 improves tungro disease resistance of a rice variety BRRI dhan71 - Hore, Tapas Kumer; Inabangan-Asilo, Mary Ann; Wulandari, Ratna; Latif, Mohammad Abdul; Nihad, Sheikh Arafat Islam; Hernandez, Jose E.; Gregorio, Glenn B.; Dalisay, Teresita U.; Diaz, Maria Genaleen Q.; Ch., Balachiranjeevi; Swamy, B.P. Mallikarjuna (Springer, 2022)
Rice Tungro disease poses a threat to rice production in Asia. Marker assisted backcross breeding is the most feasible approach to address the tungro disease. We targeted to introgress tungro resistance locus tsv1 from Matatag 1 into a popular but tungro susceptible rice variety of Bangladesh, BRRI dhan71. The tsv1 locus was traced using two tightly linked markers RM336 and RM21801, and background genotyping was carried out using 7 K SNPs. A series of three back crosses followed by selfing resulted in identification of plants similar to BRRI dhan71. The background recovery varied at 91–95% with most of the lines having 95%. The disease screening of the lines showed moderate to high level of tungro resistance with a disease index score of ≤ 5. Introgression Lines (ILs) had medium slender grain type, and head rice recovery (59.2%), amylose content (20.1%), gel consistency (40.1 mm) and gelatinization temperature were within the acceptable range. AMMI and Kang’s stability analysis based on multi-location data revealed that multiple selected ILs outperformed BRRI dhan71 across the locations. IR144480-2-2-5, IR144483-1-2-4, IR144484-1-2-2 and IR144484-1-2-5 are the most promising lines. These lines will be further evaluated and nominated for varietal testing in Bangladesh.